2010
DOI: 10.3834/uij.1944-5784.2010.08.12
|View full text |Cite
|
Sign up to set email alerts
|

Malakoplakia of the Genitourinary Tract: A Report of 3 Cases

Abstract: KEYWORDS: Malakoplakia; Michaelis-Gutmann bodies; Urethral tumor; UrethralMalakoplakia is a rare chronic inflammatory disease, most commonly found in the urinary tract. It has been associated with chronic infections, malignancies, and immunocompromised states. The authors present 3 cases of malakoplakia of the genitourinary tract, seen in 3 female patients who sought medical attention due to pain or bleeding. The histopathological examination in all cases was compatible with malakoplakia and characterized by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Bhaijee et al 10 reported that prolonged cotrimoxazole therapy resolved mass caused by malakoplakia. No recurrence was detected during a 3-year follow-up 4,10,35,36 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Bhaijee et al 10 reported that prolonged cotrimoxazole therapy resolved mass caused by malakoplakia. No recurrence was detected during a 3-year follow-up 4,10,35,36 …”
Section: Discussionmentioning
confidence: 95%
“…No recurrence was detected during a 3-year follow-up. 4,10,35,36 Appropriate workup of suspicious masses consists of imaging to determine the extent of the mass, biopsy to rule out malignancy, histopathological review for the presence of Michaelis-Gutmann bodies, and age-appropriate cancer screening. 1,14,16 Several organisms are hypothesized to play a role in the pathogenesis of malakoplakia, including E. coli, Mycobacterium tuberculosis, Proteus, and S. aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options include use of hormonal manipulation, such as tamoxifen, raloxifen or GnRH analogs, radiotherapy and arterial embolisation. 6 .…”
Section: Discussionmentioning
confidence: 99%
“…When a female patient come with such symptom a detailed history and examination is necessary. A simple pelvic examination may reveal the cause ofdysuria in some case.Physical examination including specular examination of the vagina and urethra may reveal causes of dysuria that are not related to urinary tract infections 6 .…”
Section: Discussionmentioning
confidence: 99%